A comparative study of Balochi and English voiced stops - Syed, Dr Nasir Abbas; Hasan, Dr Gul; Khan, Daulat (Hanken, 2015)
There is a vast literature on the study of voice onset time for plosives in the world language. But no such literature is available on Balochi. Besides, most of the available research on VOT focuses on voiceless stops. The current study focuses on VOT of voiced stops of Balochi and English in comparative perspective. Two groups of Balochi speakers were recorded for this study. The first group comprised of ten Balochi speakers from Turbat and who produced words of Baloch starting with voiced stops. Twelve adult Baloch learners of English living in London were asked to produce words of English starting with voiced stops of English. An acoustic analysis of the recordings confirm that Balochi is a voicing language. Place of articulation and adjacent vowel have strong influence on VOT of voiced stops. The current study also re-affirms the previous findings that speakers of a voicing language find it very hard to produce voiced stops of an aspiration language accurately. The participants of the current study were found to transfer L1 VOT values in production of voiced of English.